Impact of Inhaled Cymbopogon Citratus Essential Oil on Lower Frequency Brain Waves through Quantitative EEG Analysis in healthy volunteers: A Self-controlled Study - Israt Jahan; Md Shaiful Islam Patwary; Esaba Sadia; Marefa Tuz Zohora Lima; Farjana Boby (Central Medical College Journal, 2025)
Background: This research delves into the intriguing question of how aromatic stimulation impacts brain activity, with a focus on alterations in lower frequency brain waves (delta and theta) across different brain regions. Using Quantitative Electroencephalogram (QEEG), this study examines the effects of exposure to the scent of Cymbopogon Citratus essential oil. Objective: To assess the influence of inhaling the aroma of Cymbopogon Citratus essential oil on EEG patterns in awake, healthy female adults, utilizing power spectral analysis. Method: In this self-controlled experiment, 30 healthy adult female participants were exposed to a water mist as a control following baseline recordings. Subsequently, participants inhaled aromatic mist from the room air, and brain activity was recorded again using QEEG. Data were collected from scalp electrode readings and compared before and after exposure to the aroma using the Wilcoxon Matched-Pairs Signed Rank Test. Result: Significant increment (p= <0.0001) of absolute delta power in parietal and temporal region along with raised absolute theta power in central, parietal, temporal and occipital brain regions observed. Conclusion: Inhalation of C. citratus essential oil elicits relaxing effects on the brain, providing insight into its potential as a natural relaxation aid. Central Medical College Journal Vol 8 No 2 July 2024 Page: 82-86